Binding properties of sterol carrier protein 2 (SCP2) characterized using Laurdan - Gianotti, Alejo Román (2018)
Sterol carrier protein 2 (SCP2) binds lipids with high affinity and broad specificity. The overall hydrophobicity, fluidity, and dipolar dynamics of the binding site of SCP2 from Yarrowia lipolytica were characterized using the environmentally-sensitive fluorescent probe Laurdan. The study revealed a binding site with an overall polarity similar to that of dichloromethane and an internal phase comparable to that of phospholipid membranes with coexisting solid-ordered and liquid-crystalline states. The fluorescence properties of bound Laurdan also revealed that the binding site of SCP2 can accommodate competitively more than one ligand, with micro and nanomolar dissociation constants. The much higher affinity for the second than for the first ligand implies that the most prominent SCP2 species in the cellular context are those occupied by two ligands. Thus SCP2 may carry a highly populated lipid in the background and a second one, specific for the functional purpose of SCP2. Our findings are important for the characterization of SCP2 biological functions and the design of specific inhibitors.